Impact of Virtual Reality Training on Pain, Forward Head Posture and Functional Outcome in Patients with Cervical Radiculopathy - Mohamed, Mohamed M.; Badawy, Mohamed S.; Fahmy, Ebtesam M.; Mohamed, Mohammed A.M. Sarhan; Abdelmageed, Shaima M. (Journal of Neonatal Surgery, 2025)
Background: Cervical radiculopathy (CR) encompasses a range of symptoms caused by the compression or irritation of nerve roots within the cervical spine. Forward Head Posture (FHP) is a common musculoskeletal condition. Virtual Reality (VR) Training presents an innovative and potentially effective method for delivering physical therapy interventions. Purpose: This study aimed to investigate the effect of VR training on pain, forward head posture and functional outcome in patients with cervical radiculopathy. Methods: Forty patients of both genders diagnosed with cervical radiculopathy participated in this study. The participants' ages ranged from 35 to 50 years, with a body mass index (BMI) not exceeding 30 kg/m². Patients were randomly assigned to study and control groups. Both groups underwent a selected physical therapy program that included electrotherapy, manual therapy, and strengthening exercises. The study group additionally received VR training. Visual Analogue Scale (VAS) was used to assess pain intensity; Kinovea software was used to measure Craniovertebral Angle (CVA); and Neck Disability Index (NDI) was used to evaluate functional outcome. Treatment was conducted three sessions per week over a duration of six weeks. Assessment of all variables was done before and after completion of treatment. Results: There were no statistically significant differences between both groups in pretreatment mean values of all measured variables (VAS, CVA and NDI). In within-group comparison, all outcome measures demonstrated significant improvement in both the study and control groups after treatment (p < 0.001). Between-groups comparison revealed statistically significant differences across all outcome variables post treatment, favoring the study group (P< 0.05). Conclusion: Virtual Reality (VR) training serves as an effective intervention for alleviating pain, correcting forward head posture, and enhancing functional outcomes in individuals with cervical radiculopathy. The immersive and engaging characteristics may improve patient adherence and motivation, positioning it as a promising adjunct to specific physical therapy programs.